Regional Differences in Individualism in Japan: Scoring Based on Family Structure - Ogihara, Yuji (Frontiers in Psychology, 2020)
The present article reported regional (prefecture-level) differences in individualism in Japan based on family structure in 2005, 2010 and 2015. Previous research calculated 2005 prefecture-level scores of individualism-collectivism in Japan by analyzing five validated indicators of individualism-collectivism (divorce rate, percentage of people living alone, percentage of elderly people aged over 65 living alone, percentage of nuclear family households, and percentage of three-generation households). However, only the scores for 2005 had been presented. The scores and their regional differences may have changed over time. Therefore, the current article calculated individualism scores for 2010 and 2015 following previous research. Analyses showed that the scores were stable over time, indicating that regional differences in individualism were maintained for this period. This report is useful for understanding regional differences in psychological phenomena and validating new indicators at the regional level.